Figuring Out Gas and Galaxies in Enzo (FOGGIE). IX. The Angular Momentum Evolution of Milky Way–like Galaxies and Their Circumgalactic Gas - Raymond C. Simons; Molly S. Peeples; Jason Tumlinson; Brian W. O’Shea; Cassandra Lochhaas; Anna C. Wright; Ayan Acharyya; Ramona Augustin; Kathleen A. Hamilton-Campos; Britton D. Smith; Nicolas Lehner; Jessica K. Werk; et al. (The Astrophysical Journal, 2025)
We investigate the coevolution of the angular momentum of Milky Way–like galaxies, their circumgalactic gas, and their dark matter halos using zoom-in simulations from the Figuring Out Gas and Galaxies in Enzo suite. We examine how the magnitude and orientation of the angular momentum vary over time within the halo and between the components of mass. From z  ∼ 2 to today, and in general across the simulated halos, the specific angular momenta of the central galaxies and the cool gas in their circumgalactic media ( T  < 10 ^5 K) increase together. Over that same period, the specific angular momenta of the hot (>10 ^6 K) and dark components of the halo change minimally. By z  ∼ 1, the central galaxies have generally lost association with the angular momentum of their full dark matter halo, both in magnitude and orientation. We find a wide distribution of angular momentum orientations in the halo, varying by up to 180° over small (∼tens of kiloparsecs) scales and between the different components of mass. The net angular momenta of the galaxies, their circumgalactic gas, and their dark matter halos are generally misaligned with one another at all cosmic times. The present-day orientation of the central galaxies is established at late times (after z = 1), after the rates of cosmic accretion and mergers decline and the disks are able to settle and stabilize their orientation.